Evaluate the Relationship between Seismic Demand and Some Seismic Intensity Indexes in a Model of Local Bridges - حسين حنان (Latakia University Journal -Engineering Sciences Series, 2023)
Linking the seismic demand imposed on structures due to earthquake to a seismic intensity index is essential in the performance-based seismic engineering methodology, but it is important to choose the appropriate index, as the most suitable index for one type of structures may be less suitable for another. In this research, the relationship between seismic demand and six different seismic intensity indexes was evaluated in a model of multi-span simply supported concrete bridges, that by studying five bridges that differ from each other only in the length of the bridge. The seismic demand resulting from 60 different seismic intensities were obtained based on the nonlinear static procedures performed in the longitudinal and transverse directions of the bridges. As a result, we found that the six studied indexes are very acceptable to use in the relationship of seismic demand for this type of bridge, but the peak ground acceleration is the least suitable, while 1.0-sec period spectral acceleration is an excellent index if we take into account the quality of suitability and ease of use.